External debt sustainability :evidence from 19-selected Asian countries - Jenny,, Lai Ching Jun. (Universiti Malaysia Sarawak, UNIMAS, 2009)
The main purpose of this study is to analyze the sustainability of external debt in 19-selected Asian countries namely, Bangladesh, Bhutan, China, India, Indonesia, Iran, Jordon, Laos, Malaysia, Maldives, Nepal, Oman, Pakistan, Philippines, Sri Lanka, Syrian, Thailand, Turkey and Vietnam. External debt data spanning from 1981 until 2006 is utilized for the stationary tests. The data was converted into ratio of external debt to GDP before the empirical analysis. We applied a formal framework based on the government’s intertemporal budget constraints (GIBC). This study found that the external debt to GDP ratios in the univariate unit root tests were stationary at first difference, which is I(1). Panel unit root tests had been used due to the low statistical power of univariate unit root test. From the findings, it was found that there are three results had been obtained which include stationary, non- stationary and inconclusive. Hence , SURADF test had been used to solve the problems of obtaining those ambiguous pictures. The results for the test supported that 9 of the 19 selected Asian countries’ external debt is sustainable. Bangladesh, Bhutan, Indonesia, Iran, Jordan, Malaysia, Nepa l, Syrian and Turkey had proved having ‘strong’ form of external debt sustainability in the test.